Fatty acid profile of Gammarus locusta newly hatched offspring from the wild and from adults farmed on mono-specific macroalgal diets - Sousa, João P.; Marques, Luísa; Rodrigues, Daniela P.; Rey, Felisa; Albuquerque, Manuel; Domingues, Maria Rosário M.; Duarte, Rafael C.; Calado, Ricardo (Frontiers in Marine Science, 2025)
The accelerated growth of marine aquaculture targeting species that require formulated aquafeeds creates a pressing need to find new sustainable ingredients and additives that can secure a premium farming performance, as well as the nutritional value of farmed species. Marine gammarid amphipods can be an excellent source of essential fatty acids (FA), namely, long-chain n-3 polyunsaturated FA (LC-PUFA). However, their potential contribution to aquaculture feeds remains largely unexplored. The present work evaluated the effect of five mono-specific macroalgal diets (Ulva sp., Fucus sp., Laminaria sp., Gracilaria sp., and Chondrus sp.) on the FA composition of the offspring of Gammarus locusta fed on these macroalgae and compared it with the offspring of wild conspecifics. Results revealed that offspring from wild G. locusta showed the highest amount of PUFA (4.95 ± 0.31 μg mg-1 DW), as well as essential FA, namely eicosapentaenoic acid (EPA, 20:5n-3) (2.49 ± 0.21 μg mg-1 DW) and docosahexaenoic acid (DHA, 22:6n-3) (0.87 ± 0.16 μg mg-1 DW). The treatment with the highest amount of PUFA and EPA was the one using Fucus sp. as a mono-specific macroalgal diet (4.46 ± 0.31 μg mg-1 DW and 2.42 ± 0.24 μg mg-1 DW, respectively). The best levels of DHA in offspring were recorded for specimens feeding on Chondrus sp. (0.56 ± 0.10 μg mg-1 DW). Significant differences in the abundance of stearic acid (18:0) and DHA were observed between the offspring of adults fed algal-based diets and those from the wild. These findings suggest that G. locusta selectively conserves and directly or indirectly biosynthesises essential FA for growth and reproduction, particularly LC-PUFA. Overall, G. locusta can perform a trophic upgrade of its diet, making this gammarid amphipod a promising additive for the formulation of high-quality aquafeeds supplying LC-PUFA.